On the anomalous features of the geomagnetic quiet-day field variations at Nagpur, India - Chandrasekhar, E.; Alex, S. (My University, 1996)
The quiet-day geomagnetic field variation data from the recently commissioned Nagpur geomagnetic observatory, which has augmented the currently active latitudinal chain of Indian magnetic observatories, are analysed for the year 1993- The variations for diurnal frequencies (Sq) recorded at Nagpur do not follow the expected trend with latitude. This is most conspicuous in the northward horizontal (X) component. The anomalous behaviour at Nagpur is also seen in the diurnal harmonic amplitudes when compared with those of the neighbouring stations Alibag (south of Nagpur) and Ujjain (north of Nagpur). This behaviour is attributed to the presence of electrically conducting anomalous sources in the vicinity of Nagpur. The anomalous internal source is inferred to be located at relatively shallower depths and is highly localized.
Keywords: Nagpur observatory; Sq variations; Geomagnetic quiet day; Diurnal harmonic amplitude